Knowledge, attitude, belief, and practice in relation to leptospirosis prevention among urban residents in selected townships in Hulu Langat, Selangor, Malaysia - Abdullah, Nurul Munirah (2018)
Leptospirosis endemicity has been affecting people’s health and their livelihoods. In Malaysia, it is still considered to be underreported and cases are prevalent in Selangor. Since leptospirosis is a great depiction of the complexity surrounding the disease transmission between humans, animals and the ecosystem, an effective prevention would require awareness of the public regarding the disease. Surveys would be used to evaluate behaviours, awareness and mindset in general prior to initiating any intervention measure. This study determined the knowledge, attitude, belief, and preventive practice (KABP) among urban residents in Hulu Langat, where leptospirosis was most prevalent. Then, association between KABP with respondents’ sociodemographics and risk factors was also determined. This cross-sectional study involved 315 healthy adolescents from urban residential areas in Hulu Langat drawn using multi stage cluster sampling method. A validated questionnaire consisted of leptospirosis-related questions was administered to respondents to explore the insights of urban residents regarding leptospirosis prevention. The data was analysed using Statistical Package for Social Sciences (SPSS) version 22.0. Descriptive analysis was presented as frequencies (%) and χ2 test was used to analyse the association between KABP and both sociodemographics and risk factors. Then, significant predictors influencing KABP were identified. Majority of respondents were Bumiputra with a mean age of 32.5 (SD 13.0) years. Of 315, only 19.7% of respondents had good knowledge, while 87.0% showed good attitude and 91.1% showed good practice in avoiding to eat or drink while handling waste. However, 56.2% of them had poor belief. The regression analysis then identified age (p = 0.005; 95% CI = 1.298, 4.396) as the significant predictor influencing overall knowledge of respondents. Respondents’ monthly income (p = 0.012; 95% CI = 0.322, 0.868) and their awareness of open waste dumping sites (p = 0.013, 95% CI = 1.138, 2.918) also influenced their overall belief. Meanwhile, respondents’ education level (p = 0.024; 95% CI = 1.109, 4.352) was the significant predictor influencing overall practice. The current findings identified weakness in respondents’ knowledge and belief despite exhibiting good attitude and preventive practice. This indicates the importance of integration of knowledge, attitude and belief into forming an acceptable practice to reduce transmission of leptospirosis among urban population in Selangor.